Immune screening identifies novel T cell targets encoded by anti-sense reading frames of HIV-1 - Berger, Christopher T.; Llano, Anuska; Carlson, Jonathan M.; Brumme, Zabrina L.; Brockman, Mark A.; Cedeno, Samandhy; Harrigan, P. Richard; Kaufmann, Daniel E.; Heckerman, David; Meyerhans, Andreas; Brander, Christian (Journal of Virology, 2015)
Cytotoxic T-lymphocyte (CTL) responses to epitopes in alternative HIV reading frames have been reported. However, the extent of CTL responses to putative proteins encoded in anti-sense reading frames is unknown. Using sequence alignments and computational approaches, we here predict five potential anti-sense HIV proteins and characterize common CTL responses against them. Results suggest that anti-sense-derived sequences are commonly transcribed and translated and could encode functional proteins that contain important targets of the anti-HIV cellular immunity.